Predictors of persistent detrusor overactivity in women with pelvic organ prolapse following transvaginal mesh repair. Issue 4 (19th January 2016) - Liang, Ching‐Chung; Hsieh, Wu‐Chiao; Lin, Yi‐Hao; Tseng, Ling‐Hong
Abstract: Aim: The aim of this study was to investigate the contributing factors of persistent detrusor overactivity (DO) in women with advanced pelvic organ prolapse (POP) after transvaginal mesh (TVM) repair. Methods: We retrospectively evaluated consecutive patients with DO and advanced POP who had undergone TVM in a tertiary hospital between 2010 and 2014. All patients received evaluations, including a structured urogynecological questionnaire, pelvic examination using the POP‐Quantification System, scores of the Urogenital Distress Inventory and Incontinence Impact Questionnaire, and urodynamic testing before TVM repair and 6 months after surgery. Patient demographics, lower urinary tract symptoms, including urinary urgency, incontinence and frequency, and urodynamic findings were analyzed between women with and without persistent DO at 12 months after surgery. Results: Of 326 patients with POP who underwent TVM repair, 63 with preoperative DO were included. Urinary urgency was present in 27 (42.9%), and urgency incontinence was present in 26 (41.3%) patients. Nineteen (30.2%) patients had persistent DO after surgery. Patients with persistent DO had lower preoperative maximal flow rate (MFR), higher preoperative detrusor pressure at maximum flow, higher postoperative residual urine volume and higher rates of concomitant sacrospinous ligament suspension compared to those without DO. In the multivariate analysis, preoperative MFR and concomitant sacrospinous ligament suspension were associated with persistent DO. Conclusion: Twenty percent of women with advanced POP had DO, and most of these cases resolved after prolapse repair. For women with lower preoperative MFR and concomitant sacrospinous ligament suspension, preoperative counseling should consist of a discussion about persistent DO and relevant urinary symptoms following TVM repair.